Can we ring the Liberty Bell? - Rustad, Martha E. H. 1975- (Cloverleaf books. Our American symbols, 2015)
Do you know when the Liberty Bell was rung for the last time? Or why it has a huge crack? Join Mr. Chen's class as they take a field trip to find out the facts about this important US symbol. Ranger Marcela explains who made the Liberty Bell, what words appear on it, and how it got its name.